2023
DOI: 10.1101/2023.03.14.532654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speed-dependent optimization of gravity effects for motor control

Abstract: Several sensorimotor control studies have provided evidence supporting that the central nervous system optimizes gravity effects to minimize muscle effort. Recently, this hypothesis has been supported by the consistent observation of direction-specific negative epochs in the phasic electromyographic signal of antigravity muscles during vertical arm movements. This suggests that gravity torque is harvested to produce some of the arm motion. However, further investigation is needed to more finely understand how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Because the tonic electromyogram (EMG)—i.e., the muscle activity that is hypothesized to compensate for gravity torque—is subtracted from the full EMG signal to obtain phasic EMG (Flanders and Herrmann, 1992; Buneo et al, 1994; Flanders et al, 1994), negative phasic EMGs mean that muscular activity is not sufficient to compensate gravity torque and thus that gravity torque participates in the arm’s motion (Gaveau et al, 2021). The existence of these negative phases has been experimentally observed in the deceleration phase of upward movements and in the acceleration phase of downward movements, thereby supporting the model’s predictions (Gaveau et al, 2021; Poirier et al, 2022, 2023b, 2023a). Consequently, directional asymmetries and negatives epochs on phasic EMG are thought to represent the hallmark of the gravity-related effort-optimization process.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…Because the tonic electromyogram (EMG)—i.e., the muscle activity that is hypothesized to compensate for gravity torque—is subtracted from the full EMG signal to obtain phasic EMG (Flanders and Herrmann, 1992; Buneo et al, 1994; Flanders et al, 1994), negative phasic EMGs mean that muscular activity is not sufficient to compensate gravity torque and thus that gravity torque participates in the arm’s motion (Gaveau et al, 2021). The existence of these negative phases has been experimentally observed in the deceleration phase of upward movements and in the acceleration phase of downward movements, thereby supporting the model’s predictions (Gaveau et al, 2021; Poirier et al, 2022, 2023b, 2023a). Consequently, directional asymmetries and negatives epochs on phasic EMG are thought to represent the hallmark of the gravity-related effort-optimization process.…”
Section: Introductionsupporting
confidence: 75%
“…It was recently shown that phasic EMG activity of antigravity muscles consistently exhibits negative epochs during vertical arm movements (Gaveau et al, 2021; Poirier et al, 2022; 2023a; 2023b) when the arm’s acceleration sign is coherent to gravity’s – i.e., in the acceleration phase of downward movements and in the deceleration phase of upward movements). Model simulations demonstrated that the negativity of antigravity muscles reflects an optimal motor strategy where gravity force is harvested to save muscle force.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations